Impact of Using Indirect Left-turns on Signalized Intersections - Taha, Mahmoud Ahmed (2015)
A Master of Science thesis in Civil Engineering by Mahmoud Ahmed Taha entitled, "Impact of Using Indirect Left-turns on Signalized Intersections," submitted in June 2015. Thesis advisor is Dr. Akmal Abdelfatah. Soft and hard copy available.